2004
DOI: 10.4049/jimmunol.173.2.1166
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Is the Signaling but Not the Lipopolysaccharide Uptake Receptor

Abstract: TLR4 is the primary recognition molecule for inflammatory responses initiated by bacterial LPS (endotoxin). Internalization of endotoxin by various cell types is an important step for its removal and detoxification. Because of its role as an LPS-signaling receptor, TLR4 has been suggested to be involved in cellular LPS uptake as well. LPS uptake was investigated in primary monocytes and endothelial cells derived from TLR4 and CD14 knockout C57BL/6 mice using tritiated and fluorescein-labeled LPS. Intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 33 publications
6
99
1
Order By: Relevance
“…Originally cloned as the only known receptor for LPS residing on the surface of cells and in serum, CD14 is now thought to form a complex with MD-2 and TLR4, through which a signal is propagated [22]. In mediating the recognition of LPS by TLR4, CD14 was believed to function mostly as an uptake protein [23]. However, recent reports indicate that the role of CD14 in LPS signaling could be more sophisticated and present evidence that CD14-TLR4 signaling permits a MyD88-independent TLR4 response [24].…”
Section: Discussionmentioning
confidence: 99%
“…Originally cloned as the only known receptor for LPS residing on the surface of cells and in serum, CD14 is now thought to form a complex with MD-2 and TLR4, through which a signal is propagated [22]. In mediating the recognition of LPS by TLR4, CD14 was believed to function mostly as an uptake protein [23]. However, recent reports indicate that the role of CD14 in LPS signaling could be more sophisticated and present evidence that CD14-TLR4 signaling permits a MyD88-independent TLR4 response [24].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that LBP is also part of the LPS clearance mechanism and that this pathway bifurcates after binding to mCD14. A more recent publication delineated that TLR4 is responsible for LPS signaling while LPS neutralization is mediated by other receptors in vitro (30). Using murine blood monocytes and endothelial cells, Dunzendorfer et al (30) demonstrated that LBP contributes substantially to the neutralization of LPS via transfer to CD14 as well as to other anionic structure binding receptors, presumably SRs.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown recently that Btk was involved in NFB activation in macrophages stimulated by LPS (9,10). However, LPS binds both TLR4 and CD14 (11,12), hence making it ambiguous whether Btk is indeed involved in TLR signaling per se. Moreover, most studies of Btk involvement in TLR signaling had been done in macrophages and dendritic cells (13)(14)(15), and it is not clear if Btk is involved in TLR signaling in B cells.…”
Section: B Lymphocytes Express Both B Cell Receptor and Toll-like Recmentioning
confidence: 99%